Penerapan Model Pembelajaran Kooperatif Tipe Group Investigation untuk Meningkatkan Minat dan Hasil Belajar Biologi Siswa SMA - Pitriani Hulu; Desman Telaumbanua (GEN BIONIX: Jurnal Ilmiah Pendidikan Biologi, 2023)
This study aims to analyze the effectiveness of the cooperative learning model Group Investigation in improving students’ interest and learning outcomes in Biology. The research employed a Classroom Action Research (CAR) design conducted in two cycles, involving 21 students of grade XI. Each cycle consisted of planning, action, observation, and reflection stages. Data were collected using observation sheets, questionnaires, tests, and interviews. The results showed a significant improvement in the learning process, students’ interest, and cognitive achievement. In Cycle I, students’ active participation reached 59.23%, which increased to 85.57% in Cycle II. Students’ learning interest also improved from 69.83% (moderate category) to 86.76% (very good category). In terms of learning outcomes, the average score increased from 68.70 in Cycle I to 80.10 in Cycle II, while classical completeness improved from 61.90% to 85.71%. These findings indicate that the implementation of the Group Investigation model effectively enhances both affective and cognitive aspects of learning. Therefore, this model is recommended as an innovative strategy to create an interactive and student-centered Biology learning environment.